Muslims in Kenyan Politics : Political Involvement, Marginalization, and Minority Status - Ndzovu, Hassan J. (Book collections on Project MUSE., 2014)
Muslims in Kenyan Politics explores the changing relationship between Muslims and the state in Kenya from precolonial times to the present, culminating in the radicalization of a section of the Muslim population in recent decades. The politicization of Islam in Kenya is deeply connected with the sense of marginalization that shapes Muslims' understanding of Kenyan politics and government policies. Kenya's Muslim population comprises ethnic Arabs, Indians, and black Africans, and its status has varied historically. Under British rule, an imposed racial hierarchy affected Muslims particularly, thwarting the development of a united political voice. Drawing on a broad range of interviews and historical research, Ndzovu presents a nuanced picture of political associations during the postcolonial period and explores the role of Kenyan Muslims as political actors.